REVEALING OPTIMAL FINANCIAL EFFICIENCY AND EFFECTIVENESS IN INDONESIAN VILLAGE GOVERNANCE - Purwanti, Dewi; Nurdini , Puji Nadiya; Suherman , Acep (Journal of Economic and Economic Policy, 2024)
General Background: Effective financial management at the village level is crucial for achieving development goals and ensuring the optimal use of allocated resources. Specific Background: This study investigates the financial performance of Waringinsari Village, located in Takokak District, Cianjur Regency, West Java, through the lens of Value for Money (VFM) for the period 2021-2023. Knowledge Gap: Previous research lacks a comprehensive analysis of village financial performance using VFM indicators, particularly in the context of rural Indonesian governance. Aims: The primary objective of this research is to evaluate Waringinsari Village’s financial performance in terms of economy, efficiency, and effectiveness, and to provide recommendations for improving financial management practices. Results: The analysis reveals that Waringinsari Village performs "Quite Economically," is "Efficient," and is "Very Effective" in its financial management. Despite this, 0.92% of the budget was unutilized in 2023. Novelty: This study offers a detailed examination of budget realization using VFM indicators in a rural Indonesian village setting, highlighting the village’s strong financial performance and the minor issue of underutilized funds. Implications: The findings suggest that Waringinsari Village should enhance its planning and budgeting processes, improve financial management discipline, and explore new income sources. Community participation, especially by the younger generation through social media, is recommended to ensure accountability and improve budget implementation. These insights can guide other villages in similar contexts towards better financial practices and development outcomes.